PENGARUH KONTEN BERITA DALAM MEDIA BOLA.COM TERHADAP KEPUASAAN PEMBACA : Survei Terhadap Pembaca Bola.com - Georgy Yesaya (2020)
This research is entitled "The Effect Of News Content In Media Bola.com on Readers Satisfaction." Media bola.com has communicative content of sports news and is equipped with aspects of news values and characteristics. Content of sport news is very interesting, which there are ornaments such as pictures, photos and videos related to what is reported, as well as realizing fulfillment of the entertainment and information needs of the reader. The research's objective is to find out whether or not there is an impact of news content in bola.com on reader satisfaction. The subject of this research is aimed at readers of bola.com, with a sample of 100 respondents. This research used the uses and gratifications theory. Researchers obtain data through surveys to bola.com readers, books, and journals on the internet. The results of the data from the survey through Google Forms are collected and then the correlation test of Pearson Product Moment, simple linear regression test, coefficient of determination test and hypothesis test. From the test of data analysis, it was found that the variabel X has a strong correlation and has a positive effect on variable Y, but the the effect is only 38,1%. So, the results of data analysis test support this research to accept Ha, which is the impact of news content in media bola.com on reader satisfaction.